Prognostic significance of p16, p21, and Ki67 expression at the invasive front of colorectal cancers. Issue 2 (9th December 2022) - Kin, Ryosuke; Hoshi, Daisuke; Fujita, Hideto; Kosaka, Takeo; Takamura, Hiroyuki; Kiyokawa, Etsuko
Abstract: Cancer cells at the invasive front are believed to be responsible for invasion/metastasis. This has led to examining various morphological features and protein expressions at the invasive front. However, accurate assessment of the pathological section requires long‐time training, and inter‐observer disagreement is problematic. Immunohistochemistry and digital imaging analysis may mitigate these problems; however, the choice of which proteins to stain and the best analysis method remains controversial. We used the "go‐or‐grow" hypothesis to select markers with the greatest prognostic relevance. Importantly, nonproliferating cells can migrate. We used Ki67 as a proliferation marker, with p16 and p21 designating nonproliferating cells. We established a semi‐automated quantification workflow to study protein expression in serial pathological sections. A total of 51 patients with completely resected colorectal cancer (stages I–IV) were analyzed, and 44 patients were followed up. Patients with cancer cells with p16‐high/p21‐low or p21‐low/Ki67‐low at the deepest invasive front demonstrated a significantly worse prognosis than those who did not display these characteristics. These results suggest that the nonproliferating cancer cells at the invasion front possess invasion/metastatic property with heterogeneity of senescence.